Pembelajaran Diferensiasi : Pengembangan Kemampuan Kognitif dan Sosial Siswa SD - Ahmad Ruslan; Widia Ardana; Erina Kartika Marta Sunjaya (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Every student has different learning needs. Students have the right to receive learning needs that are appropriate to their individual development. One of the learning models that supports students is differentiation learning. Differentiated learning is a pedagogical approach designed to meet diverse learning needs among students by adapting methods, materials and learning environments. This article discusses how differentiated learning can develop students' cognitive and social abilities in elementary schools. This type of research article uses a qualitative approach with a literature review method. This literature comes from research results limited to articles from the last 10 years.